PENGARUH PERAWATAN NESTING DAN POSISI PRONASI TERHADAP PENURUNAN SKOR DOWNES PADA BAYI PREMATUR DENGAN DISTRES NAPAS DI RUANG PERINATOLOGI - Mena Okta Yosvita; Eli Lusiani; Maya Amalia (Forind Press, 2026)
Preterm infants are at high risk of respiratory distress due to surfactant deficiency, and conventional supportive management involving mechanical ventilation and high-concentration oxygen therapy may impose additional physiological stress. Developmental care through a combination of nesting and prone positioning has been proposed as a non-pharmacological intervention to stabilize physiological function in preterm infants, yet evidence regarding its effectiveness in reducing Downes scores within the Indonesian clinical setting remains limited. This study aimed to determine the effect of nesting care and prone positioning on the reduction of Downes scores in preterm infants with respiratory distress in the Perinatology Ward of RSUD Al Ihsan. A quasi-experimental design with a non-equivalent control group approach was employed, involving 20 preterm infants (10 in the intervention group and 10 in the control group) selected through purposive sampling according to inclusion and exclusion criteria. The intervention group received nesting and prone positioning for two hours, while the control group received no intervention. Downes scores were measured before and after the observation period using a standardized observation sheet and analyzed using the Wilcoxon test. The results showed that all respondents (100%) in the intervention group experienced a reduction in Downes score, with a mean rank of 5.50 compared to 4.50 in the control group, yielding a p-value of 0.014 (α=0.05), leading to rejection of H0. This study concludes that nesting care combined with prone positioning significantly affects the reduction of Downes scores in preterm infants with respiratory distress and may be considered as a standard developmental care component in perinatology units.